Las redes sociales digitales: una valoración socioeducativa. Revisión sistemática - Fuentes Cancell, Dieter Reynaldo; Estrada Molina, Odiel; Delgado Yanes, Nilda (Revista Fuentes, 2021)
La futura y ya actual revolución industrial 4.0 demanda la introducción de una transformación digital en la educación superior contribuyendo a la formación de profesionales competentes, por lo cual, en las pedagogías y tecnologías emergentes se evidencian un incremento de experiencias didácticas en el uso de las redes sociales digitales. En esta investigación se propone a partir de una revisión sistemática cuáles son las tendencias actuales del uso de las redes sociales digitales con fines educativos. Se empleó el protocolo PRISMA y se analizaron 79 trabajos presentes en la base de datos Scopus. Se concluye con la defensa de las siguientes tendencias y líneas de investigación: políticas de comunicación institucional universitaria desde los niveles macro, meso y micro del currículo; el desarrollo de la creatividad, la convergencia cultural y la diversificación mediática; la innovación educativa; la cultura mediática y la identidad digital académica. Abstract The future and already current industrial revolution 4.0 demand the introduction of a digital transformation in the higher education contributing to the formation of competent professionals, for which, they are evidenced in the and emergent technologies, an increase of didactic experiences in the use of the digital social networks. In this research a systematic review to identify current trends in the use of online social networks for educational purposes are performed. PRISMA protocol was used and analyzed 79 studies present in the database Scopus. In the systematic review, the following questions are answered: What types of designs predominate in the scientific literature? What is the dependent- independent pairs of variables? And What are the current trends in the use of digital social networks for educational purposes? As a result of this research, Facebook is reaffirmed as the social network most used by educators and the need for the integrated and varied use of these networks. It concludes with the defense of the following trends: university institutional communication policies from the curricular levels; the development of creativity, cultural convergence and media diversification; educational innovation; media culture and academic digital identity.